Developing Mathematical Devices with Characteristics Realistic Mathematics Education - Wewe, Melkior; Juliawan, I Wayan (Universitas Islam Raden Intan Lampung, INDONESIA, 2019)
This research aims to generate a mathematics learning media characterized by valid and realistic mathematics education, describes the practicality of the learning media, and measures the results of the learning media toward the students’ learning outcome. This study uses the ADDIE Model which consists of five stages, namely: analysis, design, development, implementation, and evaluation. The final products of this research are the lesson plan (RPP) and student worksheet (LKS) which are characterized by realistic mathematics education. Based on the results of the study, the validity analysis of the developed lesson plan and students’ worksheet that is categorized as valid and in accordance with the classification of a good lesson plan and students’ worksheet. After an assessment and revision of the learning media had been conducted, the implementation of the learning media was carried out. Based on the results of the analysis, the practicality of the product obtains an average score of 88.45% with the highly practical criteria. The analysis of students’ responses toward the worksheet obtains an average score of 4.08 and has fulfilled the practical criteria. The analysis of the teacher’s responses toward the worksheet obtains an average score of 4.58 and has fulfilled the practical criteria. The results of the pretest and posttest analysis show that the developed products have met the effective criteria because the percentage of students' completeness in the pretest was 58.65% and posttest was 81.9% which increased by 23.25%.